Pharmacodynamic Modeling of Sunscreens: New Efficacy Evaluation, Risks of Sunburn and Melanoma and Very Low to Very High Sun Protection Factor - Win L. Chiou (Journal of Dermatologic Research And Therapy, 2020)
Pharmacodynamic modeling of sunscreens was performed using a new concept of Skin UV Index (SUI) on the exposed skin as a parameter to evaluate the potential effectiveness of sunscreens against sun damage. The SUI predicts the UV heat intensity on the skin surface in terms of the solar UV Index at the time of the study and is calculated by solar UV Index/sunscreen’s SPF. SUI numbers for sunscreen with SPF ranging from 2 to 100 under a solar UV Index of 10 was used for illustration. Based on guidelines from WHO, Australia and New Zealand, sunscreens yielding SUI < 3 are assumed to be effective against sun damage such as sunburn and melanoma. Based on the above assumption, sunscreens with SPF > 4 were found to be effective when sunscreens were evenly applied at 2 mg/cm2. Review of numerous studies suggests that missing applications may represent a major, seemingly unavoidable, SPF-independent factor causing unintended sunburns for sunbathers in the US and other countries with a temperate climate. This might in turn become a major factor for causing exponential increase in melanoma incidence rates observed in the last few decades. For example, in an SPF 30 sunscreen study all 25 participants suffered unintended sunburns after one week of sunbathing. Also, a mean missing application of 20% of the total exposed area and a mean missing of about 50% of the time were reported in two separate studies. Simulations were also performed with under-applications of 50% and 75%. The present simulations may provide a rationale of why routine use of a low SPF 8 sunscreen was reported to be effective against melanoma in a 2018 Australian study. Based on model simulations it is proposed that in the US, SPF 8 sunscreen and SPF 2 to 6 sunscreen may be adequate for routine, unintentional use for sun-sensitive populations and non-sun-sensitive populations, respectively.
Keywords: sunscreen